Chattering suppression of the sliding mode observer for marine electric propulsion motor based on piecewise power function - Xiangfeng Li; Shengqiang Zhan; Fang Guo; Zidan Zhuang; Huitao Zhang; Hui Liao; Lili Qu (Frontiers in Energy Research, 2022)
The sliding mode observer (SMO)–based sensorless control is essentially a discontinuous switching control algorithm. Therefore, there is large speed or torque chattering in the permanent magnet synchronous motor (PMSM) with existing sliding mode observer–based control methods. In order to solve this problem well, an algorithm based on an improved sliding mode observer is proposed. In detail, the piecewise power function approach is used to replace the traditional ones, that is, the sgn function or the sigmoid function approach. Simulation verifications are conducted to validate the effectiveness of the proposed observer. It shows that the piecewise power function–based sliding mode observer algorithm has obvious advantages in the stability of the three-phase current, namely, it improves the estimation accuracy of the rotor position, rotor speed, and dynamic response to various loads. For further verification, the proposed sliding mode observer algorithm is implemented and verified in a marine electric propulsion motor with a DSP chip of TMS320F28377D. Experimental results validate that the piecewise power function–based sliding mode observer algorithm has high control accuracy and fewer fluctuations, which are all vital in marine engineering.